Advancing Microgrid Resilience Through Vehicle-to-Grid Integration: A Review of Current Trends and Future Directions - Akash, Khairul Bashar; Ahmed, Shishir; Emon, Md Afrad Hasan; Shifat, Sk Md Raihan (Control Systems and Optimization Letters, 2025)
The integration of vehicle-to-grid (V2G) technology within microgrids is emerging as a transformative solution to enhance the resilience, reliability, and efficiency of modern energy systems. With electric vehicle (EV) adoption accelerating worldwide, V2G allows EVs to function not only as transportation assets but also as mobile, bidirectional energy storage resources capable of strengthening grid flexibility. By enabling EVs to discharge electricity back into the grid, V2G systems contribute to critical grid services such as peak shaving, load leveling, frequency regulation, and emergency backup during power disruptions. For microgrids, which are decentralized energy systems designed to operate either independently or in coordination with the main grid, the integration of V2G significantly improves stability, demand management, and the capacity to supply critical loads under adverse conditions. This dual functionality positions V2G as an important enabler of resilient, community-based energy networks. Nevertheless, widespread deployment faces challenges, including concerns over battery degradation, the absence of standardized interoperability, high infrastructure and implementation costs, and regulatory and market uncertainties. Furthermore, the full potential of V2G relies heavily on advancements in communication protocols, optimization-based energy management strategies, and intelligent control algorithms that can balance user preferences with system needs. This review examines the present state of V2G integration in microgrids, outlining its advantages, barriers, and future research directions, while emphasizing the importance of supportive regulations, large-scale pilot projects, and continued technological innovation in enabling the transition toward decentralized, decarbonized, and digitized energy systems